Benefits of stroke treatment delivered using a mobile stroke unit trial. Issue 3 (April 2018) - Yamal, Jose-Miguel; Rajan, Suja S; Parker, Stephanie A; Jacob, Asha P; Gonzalez, Michael O; Gonzales, Nicole R; Bowry, Ritvij; Barreto, Andrew D; Wu, Tzu-Ching; Lairson, David R; Persse, David; Tilley, Barbara C; et al.
Rationale: Mobile stroke units speed treatment for acute ischemic stroke, thereby possibly improving outcomes. Aim: To compare mobile stroke unit and standard management clinical outcomes, healthcare utilization, and cost-effectiveness in tissue plasminogen activator-eligible acute ischemic stroke patients calling 911. Sample size: 693. Eighty percent power with 0.05 type I error rate to detect a difference of 0.09 in mean utility-weighted modified Rankin scale between groups. Design: Phase III, multicenter, prospective cluster-randomized (mobile stroke unit versus standard management weeks) comparative effectiveness study in tissue plasminogen activator-eligible patients. Outcomes: Primary: Ninety-day mean utility-weighted modified Rankin scale. Coprimary: cost-effectiveness based on EQ5D quality of life and one year poststroke costs. Analysis: Two-sample t-test and linear regression adjusting for covariates; incremental cost-effectiveness ratio and net benefit regression. Results: As of March 2017, 288 tissue plasminogen activator-eligible patients have been enrolled (173 in the mobile stroke unit arm and 115 in the standard management arm). Two new centers start in early 2017 with target end of recruitment September 2019. Conclusion: This is the first randomized study to test for disability, healthcare utilization, and cost-effectiveness of a mobile stroke unit. The progress of the study suggests that it is feasible. Management of tissue plasminogen activator eligible acute ischemic stroke patients by a mobile stroke unit could potentially result in less disability and healthcare utilization, and be cost effective. Mobile stroke units are very costly. This trial may determine if the fixed cost can be justified by a reduction in disability and healthcare utilization. Clinical Trial Registration: NCT02190500.